Climate Smart Agriculture Training Manual for Training of Trainers: Promoting Adoption of Pigeonpea, Sorghum and Pearl Millet - Saalu, Faith; Ngwira, Amos; Ganga, Rao NVPR; Rao, KPC; Jacob, Emanuel; Harawa, Rebbie (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This training manual provides knowledge and skills to government extension officers and lead farmers on the concept of climate smart agriculture to empower them to train farmers on appropriate technologies, innovations and management practices against climate change risks